Rotavirus vaccine and diarrhoeal morbidity in South Africa - Groome, Michelle Jennifer (My University, 2016)
Background Vaccination against rotavirus, the leading cause of diarrhoea in children under 5 years of age, has the potential to reduce diarrhoeal morbidity and mortality. Lower vaccine efficacy and immunogenicity were observed in clinical studies of oral rotavirus vaccines in low- and middleincome countries in Africa compared to high-income countries. The impact of routine vaccine use in African countries, where almost half of the global rotavirus deaths occur, is yet to be established. In addition, factors affecting immune responses to the rotavirus vaccine warrant further investigation. Objectives To assess the effectiveness and public health impact of introduction of the monovalent oral rotavirus vaccine into the national immunisation programme in South Africa, a setting with a high prevalence of human immunodeficiency virus infection; and to determine the effect of maternal rotavirus-specific antibodies and abstention from breastfeeding at the time of rotavirus vaccination on immune responses to the rotavirus vaccine. Methods A case-control study was used to estimate vaccine effectiveness in children under 2 years of age, with comparison of rotavirus vaccination status among rotavirus-positive diarrhoeal cases to rotavirus-negative and respiratory controls, respectively. The impact of routine rotavirus vaccination on all-cause diarrhoeal hospitalisations was assessed by comparing the incidence before and after vaccine introduction among HIV-infected and HIV-uninfected children under 5 years of age. HIV-uninfected mother-infant pairs were randomised to either abstention from breastfeeding or unrestricted breastfeeding at the time of rotavirus vaccination to assess the effect of breast milk on the immune response to the vaccine; in addition maternal rotavirus serum antibodies were measured. Results Two doses of rotavirus vaccine provided protection of 57% (95% CI 40–68) against hospitalisation for acute rotavirus diarrhoea. Protection extended through the first 2 years of life and the vaccine protected against different rotavirus strains. Routine vaccine introduction was temporally associated with a 34% to 57% decrease in the overall incidence of all-cause diarrhoeal hospitalisations in children under 5 years of age during 2010–2014 compared to prevaccination years (p<0.001).The greatest reductions were observed in children under 12 months of age. Reductions were maintained for 5 years post-vaccine introduction. Abstention from breastfeeding for 60 minutes before and after each rotavirus vaccine dose showed no significant improvement in infant immune responses to the vaccine. However, mothers of infants who seroconverted after the first vaccine dose had significantly lower anti-rotavirus immunoglobulin G titres at baseline than those whose infants did not seroconvert. Conclusion Rotavirus vaccination was an effective intervention against severe diarrhoea in South African children, preventing hospitalisations due to rotavirus while also reducing diarrhoeal hospitalisations for diarrhoea of any cause. These studies add to the growing body of evidence showing that rotavirus vaccines are reducing diarrhoeal disease in low- and middle-income countries and should form part of comprehensive diarrhoeal disease control and prevention. A change in breastfeeding practice at the time of rotavirus vaccination did not improve immune responses to the vaccine, yet maternal antibodies may play an important role. Continued research is needed to optimise the protection afforded by currently licenced vaccines and to develop novel rotavirus vaccines.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2016
Keywords: Morbidity; Diarrhea; Rotavirus Vaccines